PENINGKATAN HASIL BELAJAR SERVICE BAWAH BOLAVOLI MELALUI MEDIA BOLA SPON PADA SISWA KELAS V A SDN KEDURUS III SURABAYA - DEDI PURNAMA, DIAN (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstrack The learning of PE (physical education) in elementary school has to be relevant with the characteristic, age, and child movement ability. Based on this the learning that is relevant with the characteristic of elementary school can be formed the using of learning media. The using of learning media aims to create fun learning as child characteristic. The learning media which is used in learning PE at elementary school can be like sponge ball which can be formed as the device to easier the learning process because the form and the weight of the ball is relevant to the child ability. On this, especially to volley ball learning. The aim of this research is to know the learning result of the volley ballunder hand through sponge ball media on students grade V SDN Kedurus III Surabaya. The research which is done by the researcher is the research experiment by using close research action in classroom scope  that is class action research (PTK). Subjek of this research is student grade V A SDN Kedurus III Surabaya. This thing is because of all problems appear in this class the numbers of students are 34 students. The result of the research are : In siclus 1, worked through up KKM as many as 24 students or pass point 71% it’s said the result of the implementatian of the learning method has not completed. In siclus 2, success pass KKM as many as 28 students or with average point 82%. Because the average point is bigger 75%. So on this can be said success/completed. For the average service underhand which sponge ball media the beginning study the result is bigger 38% and the ending study the result is 82% .There foretheincreasing result of theunderhand volley ball service by using sponge ball the beginning and the ending is 44%. Keywords : The learning result, the underhand Volley ball service, Sponge ball media.